(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes a narrow sector of the economy – private direct investment in small businesses, provides typical cases of default, common mistakes of private investors when interacting with small businesses; it also examines the pilot project created and examines the prospects for its application to improve professionalism in this area.